3-D kinematical analysis on left leg technique in the last exerting in javelin throwing - Zhen, J.; Xiao, T.; Zhao, H. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
Javelin throwing is a kind of event that has a completely different personality and philosophy from the heave thrower, with almost unrestricted approach run. Approach speed and timing transition of body segment play an important role to performance. Through approach, for the elite world javelin throwers, the speed that the body and javelin obtain is 7-8 m/s before exerting finally. Through exerting, the speed of weight of the body is lowered to less than 3 m/s, and javelin obtain 21 m/s above speed. Therefore, through exerting oneself finally, the speed of javelin is increased rapidly, left side planting movement enabling momentum transmit and increase javelin speed. Hence, left leg technique play a important role During transition, the planting of the left leg have a key function, through "whip" technique, the speed of lower big part of the body gradually transmit to upper small arm, via hand, to javelin at last. This study investigated left leg contribution to javelin throwing during the last thrust phase. Eight female javelin throwers were taped during selective competition of XIII Asian games in 1998. The subjects were videotaped at 50 frames per second. By analyzing left leg technique, the consciousness of left side supporting and stretching should increased, more and more coaches and athletes will pay more attention to stretching phase of left side supporting technique. The posture of the left foot falling to the ground has influence on left leg supporting technique to certain degree. Home outstanding women javelin throwers should make a little enlargement inside of angle that button up at left foot planting. Home outstanding women javelin throwers have a big buffer degree, hence make the left shoulder, left hip supported not enough. They should enhance the cowgirl muscle the cluster carrying the constringency of left shoulder crest of left shoulder; they should enhance the cowgirl muscle anti-carrying contracting training.